ANALISIS FAKTOR-FAKTOR PERUBAHAN DESAIN KEMASAN TERHADAP NILAI JUAL ABON IKAN (KASUS UD PRANSPUL, KECAMATAN SEPULU, BANGKALAN) - Raden Faridz (AGROINTEK, 2010)
The aim of this research is want to know and analyze the factors of packaging design, including: colors, shape, brand (logos) its affect to the amount of selling and its perception of PRANSPUL fried shredded fish product. The research is done in two phases, the first is to compare the amount of selling both of old packaging and new packaging product. The second is to analyze which factors influence significantly to the perception.and its regression model. The material of this research are an old and a new packagings of fried shredded fish. The packaging dimension of material (wide x height) are 15 cm x 12 cm and 10 cm x 15 cm for the old and the respectively. Two kinds of data were collected to get amount of selling and 100 responden to answer question during 2,5 months Responden are collected by accidental sampling. The result showed that the number of selling of an old packaging is 17 and the new one is 29 and significantly difference (t test). According anova the shape affect significantly (p = 0,000) and followed by merk (p=0,011) and colour (p=0,013) respectively. The influence of design of packaging factors to the perception wholely can be explained by regression model, Y = -1,687 + 0,114 colour + 0,837 shape + 0,257 logo/merk, R2 = 0,304.